Musical Creativity of the Reyog Gajah Manggolo Group at the 2022 Reyog Ponorogo National Festival - Wulan, Wulan Dwi Karlina Sari; Kiswanto, Kiswanto (Acintya, 2025)
This study aims to describe the musical presentation and analyze the creativity of the Reyog Gajah Manggolo (RGM) group from SMA Negeri 1 Ponorogo in the 2022 National Reyog Ponorogo Festival. The research employs a qualitative approach with a descriptive-analytical method. Data were collected through field observations, in-depth interviews, visual documentation, as well as document and music notation analysis. The findings reveal that the musical arrangement performed by RGM was systematically designed to support the dramatic flow of the performance. Music functioned not only as an accompaniment to dance but also played a crucial role in shaping the atmosphere and dynamics of the stage presentation. The creative process was carried out collaboratively among the coach, composer, and musicians through several stages, including planning, musical experimentation, intensive rehearsals, and a final preparation period before the festival. The creativity generated from this process brought positive impacts, both on the quality of the performance and the personal development of its members. Internally, it strengthened character, boosted self-confidence, and fostered solidarity. Externally, the group’s presence helped reinforce the role of Reyog art as a living cultural heritage within the school and the wider community. These findings indicate that musical creativity within the RGM group represents a form of traditional adaptation that aligns with contemporary developments, while also serving as an effective strategy for the regeneration and preservation of Reyog among younger generations.